Intelligence in the national security enterprise an introduction - George, Roger Z. 1949- (Georgetown University Press, 2020)
This textbook introduces students to the critical role of the US intelligence community within the wider national security decisionmaking and political process. Intelligence in the National Security Enterprise defines what intelligence is and what intelligence agencies do, but the emphasis is on showing how intelligence serves the policymaker. Roger George draws on his thirty-year CIA career and more than a decade of teaching at both the undergraduate and graduate level to reveal the real world of intelligence. The book includes useful features for students and instructors such as excerpts and links to primary-source documents, suggestions for further reading, and a glossary. *Written for upper-level undergraduates or graduate students in courses about intelligence, security studies, and US foreign policy. *Geared to instructors who want to teach how intelligence fits into the big picture of US national security decisionmaking process. *Examines the full range of intelligence support to policymakers, from strategic intelligence and warning analysis, to actionable daily intelligence, to covert action